World-class performance in lightweight rowing: is it genetically influenced? A comparison with cyclists, runners and non-athletes - Muniesa, C. A.; Gonzalez-Freire, M.; Santiago, C.; Lao, J. I.; Buxens, A.; Rubio, J. C.; Martin, M. A.; Arenas, J.; Gomez-Gallego, F.; Lucia, A. (British Journal of Sports Medicine, 2010)
In this study, genotype frequencies of several polymorphisms that are candidates to influence sports performance (ie, ACTN3 R577X, ACE ID, PPARGC1A Gly482Ser, AMPD1 C34T, CKMM 985bp/1170bp and GDF8 (myostatin) K153R) were compared in 123 nonathletic controls, 50 professional cyclists, 52 Olympicclass runners and 39 world-class rowers (medallists in world championships, lightweight category). Significant differences in genotype distributions among the groups were not found except for the ACE gene, that is, lower (p<0.05) proportion of II in rowers (10.3%) than in the total subject population (22.3%). In summary, sports performance is likely polygenic with the combined effect of hundreds of genetic variants, one possibly being the ACE ID polymorphism (at least in the sports studied here), but many others remain to be identified.